Patient functional independence and occupational therapist time-use in inpatient services: Patient demographic and clinical correlates - Bianca E Summers; Kate E Laver; Rebecca J Nicks; Nadine E Andrew; Christopher J Barr; Laura Jolliffe; Natasha A Lannin (SAGE Publishing, 2021)
Introduction Health care expenditure has rapidly increased in Australia. Effective management of occupational therapy services is required to meet clinical demand. Improving our understanding of factors which influence occupational therapy service delivery is a vital step to manage workload distribution and optimise service efficiency. This study aims to examine the influence of patient sociodemographic characteristics, diagnosis and functional independence on the utilisation of occupational therapy resources in hospital inpatients over 18 years old. Methods Prospective, cross-sectional, observational cohort study of 4549 inpatients from three hospital sites in Melbourne, Australia. Data extracted from organisational databases and included in this study were: patient demographics, diagnosis, functional level assessed using the SMAF (Functional Autonomy Measurement System) and occupational therapy time-use. Data were analysed using univariable and multivariable modelling. Results Occupational therapy time-use was significantly associated with all variables included in analysis ( p  < 0.05). For each variable the amount and direction of effect differed between hospital sites. The SMAF was the only variable consistently associated with occupational therapy time-use. Higher occupational therapy time-use was associated with lower functional independence (leading to a 3.5 min increase in median occupational therapy time for every unit decrease in SMAF score). Conclusions Management of resources within busy hospitals require knowledge of factors associated with occupational therapist time-use. This study identified that time-use could in part be predicted by functional independence, diagnosis and sociodemographic characteristics. Occupational therapy managers can use this information to support decision making while acknowledging other patient and therapist level factors also influence time-use.